Management of traumatic segmental bone loss using linear rail system, our experience at the University of Maiduguri Teaching Hospital, Maiduguri, Nigeria - Theophilus Maksha Dabkana; Friday Titus Nyaku; Bunu Bukar (Sahel Medical Journal, 2016)
Background: Following road traffic accidents (RTAs) some patients sustain fractures that involve loss of bone segments. This does not do well with the usual bone grafting. To achieve union, docking of the remaining fragments will have to be done which will lead to severe shortening. Vascularized bone graft would be the best. In the absence of vascularized bone graft, bone transport can be used to avoid the shortening and treat the defect. Objective: To assess the effectiveness bone transport/distraction technique using the Linear Rail System for the treatment of segmental bone loss following trauma. Methods: All patients with segmental bone loss of more than 4 cm following RTA were included in the study. 10 patients were involved in the study. Results: All our ten patients achieved adequate defect correction of up to 80% to 100%. Conclusion: H.S. Pitkar LRS System when used properly is good for management of segmental bone loss following trauma.